“Auditoría de gestión y su relación con la eficiencia en el área administrativa de la distribuidora Sumipam cantón Quevedo, año 2020”. - Torres Navarrete, Wilfrido Bolívar (2021)
The purpose of the management audit is to evaluate the degree of efficiency and effectiveness with which the resources are managed, therefore the present investigative work was developed in the City of Quevedo in the SUMIPAN company, with the objective of conducting a management audit at the Administrative area of the company to determine the level of efficiency and effectiveness with which the activities are fulfilled, through the objectives set it was possible to show the shortcomings that are affecting the performance of the activities taking into account the risks that arise in the company . For the development of the research, technical instruments for collecting information have been considered, which helped the development of this work, interviews with management, administrator and staff were also considered. With regard to the management of working capital, it was found that it barely covers short-term expenses due to the fact that the company does not have regulations, manuals and trained personnel in this area, it should be noted that the financial management is in charge of efficient administration of working capital within a balance of risk and profitability criteria, as well as guiding financial ability to guarantee the availability of financing sources and provide the proper record of operations as control tools. For this reason, Financial management is an essential part in the progress and economic growth of the SIMIPAN company, since at present the companies that continue to operate are the ones that best adapt to changes and make the right decisions. Keywords: Management audit, Internal control, Cash flow.